Peeling mechanics of film-substrate system with mutually embedded nanostructures in the interface. (1st September 2022) - Shui, Langquan; Yan, Weidong; Zhang, Yujie; Xu, Lihan; Gao, Enlai; Liu, Ze; Zheng, Quanshui
Abstract: Through mechanical deformation of crystalline metals with hard molds, superplastic nanomolding provides a simple and high-throughput method to directly form nanostructures in the metal surface. The releasing of the molded nanostructures generally involves in chemical etching away the mold, in which metal nanostructures could also be chemically attacked. Therefore, mechanical demoulding is very promising not only for solving the above problem, but also for drastically reducing the cost by recycling molds. As a result, the mechanics underlying the mechanical demoulding is very important and highly desired since it can tell what kind of nanofeatures can be released without damaging the molds. In this paper, we develop a theory for the peeling mechanics of elastic film with its surface nanostructures deeply embedded in a substrate. Specifically, by analyzing the obtained micromechanical behavior in the interface and combining it into the mechanical framework of the macro-bending behavior of the film, we successfully derive a nonlinear governing equation for demoulding. By non-dimensionalizing the governing equation and further numerically solving it, we find out a simple expression for the apparent adhesion work. Our theory demonstrates that the apparent adhesion work is mainly contributed by the interface shear stress rather than the interface energy as revealed by the peeling of elastic film from flat or wavy interfaces, and the fillet radius at the edge of the cavity is found to be a crucial factor to determine the success or failure of demoulding. Finally, by recording the real-time peeling force of an actual peeling process, we observe that the theoretical prediction is in good agreement with the experimental results. This work not only provides theoretical guidance for mechanical demoulding of molded micro-/nanostructures, but also establishes a mechanical framework for studying the peeling mechanics of real material interface.